Amanitins: The Most Poisonous Molecules of the Fungal World - János Vetter (Molecules, 2023)
Among the toxic metabolites of the fungal world, those that, due to their strong biological effect, can seriously (even fatally) damage the life processes of humans (and certain groups of animals) stand out. Amatoxin-containing mushrooms and the poisonings caused by them stand out from the higher fungi, the mushrooms. There are already historical data and records about such poisonings, but scientific research on the responsible molecules began in the middle of the last century. The goals of this review work are as follows: presentation of the cosmopolitan mushroom species that produce amanitins (which are known from certain genera of four mushroom families), an overview of the chemical structure and specific properties of amanitins, a summary of the analytical methods applicable to them, a presentation of the “medical history” of poisonings, and a summary of the therapeutic methods used so far. The main responsible molecules (the amanitins) are bicyclic octapeptides, whose structure is characterized by an outer loop and an inner loop (bridge). It follows from the unusual properties of amanitins, especially their extreme stability (against heat, the acidic pH of the medium, and their resistance to human, and animal, digestive enzymes), that they are absorbed almost without hindrance and quickly transported to our vital organs. Adding to the problems is that accidental consumption causes no noticeable symptoms for a few hours (or even 24–36 h) after consumption, but the toxins already damage the metabolism of the target organs and the synthesis of nucleic acid and proteins. The biochemical catastrophe of the cells causes irreversible structural changes, which lead to necrotic damage (in the liver and kidneys) and death. The scientific topicality of the review is due to the recent publication of new data on the probable antidote molecule (ICR: indocyanine green) against amanitins. Further research can provide a new foundation for the therapeutic treatment of poisonings, and the toxicological situation, which currently still poses a deadly threat, could even be tamed into a controllable problem. We also draw attention to the review conclusions, as well as the mycological and social tasks related to amanitin poisonings (prevention of poisonings).